The predicament of Young Journalists: The study of Portugal - Pacheco,Liliana (2014)
This article attempts to draw a portrait of young Portuguese journalists. Who are these young professionals dedicated to a profession which is in turmoil? The reasons for the instability of the sector are many and varied. We could mention the trend towards media concentration into business groups: the resulting mergers lead to diminish the importance of journalists, which in turn leads to contraction of the job market. An issue which is proving intractable is the job insecurity affecting mainly younger journalists - those who actually get the jobs, since there are large numbers of journalism graduates who run up against almost insurmountable barriers to make an entry into the profession. Power relations in the editing rooms are also changing. Relations with supervisors become impersonal, mediated by editors or managers who may not have an access to the board of directors. Within the profession, there are certain facets which differentiate one generation of journalists from another. The new information technologies also play an important role here: in addition to exponentially strengthening the dominance of time management, they completely transform communication models based on the traditional media. The role of the journalist becomes more elusive. In other words, the traditional mediating role of the journalist is disappearing.